Mechanics and control engineering. selected, peer reviewed papers from the 2014 3rd International Conference on Mechanics and Control Engineering (ICMCE 2014), October 26-28, 2014, Asheville, North Carolina, USA - Zhang, James; Chang, Guanghsu A.; Marburg, Steffen (Applied mechanics and materials ;, 2015)
Collection of selected, peer reviewed papers from the 2014 3rd International Conference on Mechanics and Control Engineering (ICMCE 2014), October 26-28, 2014, Asheville, North Carolina, USA. The 84 papers are grouped as follows: Chapter 1: Novel Materials and Processing Technologies; Chapter 2: General Mechanical Engineering and Applied Mechanics; Chapter 3: Power Engineering; Chapter 4: Modeling and Research of Electrical and Microstrip Circuits; Chapter 5: Sensors, Measurements and Monitoring; Chapter 6: Mechatronics Systems and Robotics; Chapter 7: Control and Automation Sciences; Chapter.